A parameter estimation program for the error-in-variable model - Tang, Shouzheng; Wang, Yonghe (Ecological modelling, 2002)
A parameter estimation method called the two-stage error-in-variable model was introduced to the models that have both dependent and independent variables subject to random errors. Even though an example was once provided to demonstrate how to use the model in a step-by-step fashion, it appears the model would not be widely applicable without the support of computer programs that can be run on either a pc or unix platform. In this study, the programming codes written in the matlab language are presented for the two-stage error-in-variable model; four estimation problems are solved with the program. It is hoped that the codes would make the method easy to use in systems ecology studies or any research involving estimation problems in which some variables are subject to errors while others have no random errors.